Designing and implementing a multi-core capable integrated urban drainage modelling Toolkit:Lessons from CityDrain3. (October 2016) - Burger, Gregor; Bach, Peter M.; Urich, Christian; Leonhardt, Günther; Kleidorfer, Manfred; Rauch, Wolfgang
Highlights: Development and application of an integrated modelling toolkit for urban water systems. Multi-core capability for high performance applications. Open source and modular design for easy and flexible extension. Abstract: Integrated urban drainage modelling combines different aspects of the urban water system into a common framework. With increasing pressures of a changing climate, urban growth and economic constraints, the need for wider spread integration is necessary in the interest of a sustainable future. Greater complexity results in greater computational burden but modelling packages will, likewise, need to be flexible enough to allow incorporation of new algorithms. With advancements in modern information technology, a parallel implementation of such a modelling toolkit is mandatory while still leaving its users the flexibility of extensions. The design and implementation of the integrated modelling framework CityDrain3 shows that it is possible to write research code that is high-performance and extensible by many research projects. Three use case scenarios are presented to showcase the application of CityDrain3. The performance advantage of parallelization (up to 40 times compared to its predecessor) and the scalability of the framework are also demonstrated.